Análise da viabilidade populacional da preguiça-comum (Bradypus variegatus Schinz, 1985) em fragmento de mata atlântica e as principais ameaças dos ambientes urbanos na Paraíba. - Pedrosa, Elaine Pessoa (2013)
The common sloth (Bradypus variegatus) has drawn attention due to the various records of isolated populations in small forest fragments and because of their presence in urban environments, causing them to be vulnerable to the effects of demographic and environmental stochasticity, inbreeding and disturbances from urban environments. The aim of this study was to analyze the population viability of the common sloth and identify the main threats to the sloths in urban environments in the Paraiba state, Brazil. We used the Vortex program version 10.1 to the Population Habitat Viability Analysis. Scenarios were built to the Minimum Viable Population (MVP), carrying capacity, reproduction and supplementation. According to our model, the population of SEMA III is smaller (n = 28) than the MVP (estimated to be n = 55) and may become locally extinct in the next 100 years. Carrying capacity (k) for population sloths at SEMA III is k = 113 and reduced viable for PMV when it is low (k = 85). Females showed a reproductive rate of 30%, but when this rate was raised to 40% in the model, the population became viable. The supplementation also depends on the female´s reproduction rate of 40%. The unviability of the population in the present scenario is due to the small population size and females’ low reproductive rate. Manage males to stay close to the females and/or introduce new males every four years will increase the females reproductive rate. In order to identify the main threats to the common sloths in the urban environment we collected information from wildlife admission records in Centro de Triagem de Animais Silvestres, Parque Zoobontânico Arruda Câmara, Área de Proteção Ambietal da Barra do Rio Mamanguape, Reserva Biológica Guaribas and from field studies in João Pessoa Square. The most impacts of records for the sloths were in urban areas (streets, squares and villages) and fewer highway (BR 101, BR 230 and PB 071). The pups were significantly impacted (x2 = 17.0, df = 1, p <0.01). Registered sloths in urban environments, suffered more impact than the sloths recorded on highways (x2 = 4.78; df = 1, p <0.02). The young also suffered major impacts in João Pessoa Square in Rio Tinto, with 84.6% of deaths. The deaths of young in the Square are related to falling trees and abandonment of mothers. Among the impacts on roads and in urban environments early withdrawal of pups of mothers seems to be the most negative impact, because the chicks don´t survive away from sloths mothers, dying shortly after being taken to CETAS.